2015
DOI: 10.5194/soil-1-527-2015
|View full text |Cite
|
Sign up to set email alerts
|

Case study of microarthropod communities to assess soil quality in different managed vineyards

Abstract: Abstract. Land use influences the abundance and diversity of soil arthropods. The evaluation of the impact of different management strategies on soil quality is increasingly sought, and the determination of community structures of edaphic fauna can represent an efficient tool. In the area of Langhe (Piedmont, Italy), eight vineyards characterized for physical and chemical properties (soil texture, soil pH, total organic carbon, total nitrogen, calcium carbonate) were selected. We evaluated the effect of two ty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 51 publications
5
25
0
Order By: Relevance
“…In this case in particular, increased sand content negatively affected the abundance of certain groups, as well as average richness and the Shannon Weaver index (the last of which, along with the Pielou equation, showed no dependence on vegetation type). Other authors (Lavelle & Spain, 2001;Gagnarli et al, 2015) have corroborated this observed influence; however, on the whole, it has not been seriously addressed in the literature.…”
Section: /9supporting
confidence: 58%
“…In this case in particular, increased sand content negatively affected the abundance of certain groups, as well as average richness and the Shannon Weaver index (the last of which, along with the Pielou equation, showed no dependence on vegetation type). Other authors (Lavelle & Spain, 2001;Gagnarli et al, 2015) have corroborated this observed influence; however, on the whole, it has not been seriously addressed in the literature.…”
Section: /9supporting
confidence: 58%
“…Vineyards often have highly degraded soils, with soil lowering up to 0.5 to 2 mm yr À1 Prosdocimi et al, 2016a), rates that vastly exceed natural rates of pedogenesis (Brevik, 2013), which is due to: i) traditional tillage management (Cerdan et al, 2010;Francone et al, 2010); ii) the application of pesticides (Marín et al, 2016); iii) low soil organic matter and water retention capacity (Brillante et al, 2015); iv) biological degradation (Costantini et al, 2015;Cagnarli et al, 2015); and, v) the impact of irrigation (Terrón et al, 2015). Most of the wine growers, local and regional governments, and viticulture companies have contributed to improve the production of wine, dissemination of tourism, promotion of vineyard landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing awareness of the need to avoid high soil erosion rates and to reduce the transfer of pollutants downstream [12,13]. To meet this goal, new agricultural measures are being applied through the development of new agri-environments with conceptual models of public spending efficiency [14] in the recovery of soil functions and services [15][16][17][18]. The occurrence of extreme rainfall events, soil characteristics and in some cases steep slopes contribute to soil degradation.…”
Section: Introductionmentioning
confidence: 99%